Designing system integration of Land Information System (LIS) for land subdivision application (PPBT) module using system integration life cycle / Nabiha Mohd Mashut - Mohd Mashut, Nabiha (2016)
This thesis presents a research project on designing system integration for Land Information System (LIS) in one module in Land Development Division (LDD) of Land office (Pejabat Tanah dan Galian, Wilayah Persekutuan Kuala Lumpur(PTGWPKL)). The module is Subdivision Land Application {Permohonan Pecah Bahagian Tanah (PPBT)) will be designed based on the System Integration Life Cycle (SILC) is analyzed in detail reflecting the quality improvement. The expected evolution of the SILC is briefly described. The basic feature of a system dealing land and utility information are computerized and data based on the computer using the Land Information System (LIS). It have limitation on that system which is the system only capable to register the application and generating letter for some purpose only. There is no integration between LDD to another unit to process the task/application and on the basis of dynamically changing data through interaction and integration between other divisions of land office.